c - d (b, 2014)
Reminiscences of A. M. A. Muhith, born in 1934, politician and economist from Bangladesh, about his friends and associates.
In Bengali; includes passages in English.
Keywords: Muhith, A. M. A., -- 1934- -- Friends and associates; Politicians -- Bangladesh -- Biography; Economists -- Bangladesh -- Biography